Fascia Lata Free Flap Anastomosed to the Superior Trochlear System for Reconstruction of the Anterior Skull Base - Reyes, Camilo; Solares, C. Arturo; Fritz, Michael A.; Groves, Michael; Bentley, Heather (Journal of Neurological Surgery Part B: Skull Base, 2017)
Objectives This study aims to introduce a novel technique for the reconstruction of the anterior skull base using a free vascularized anterolateral thigh fascia lata free flap (FLFF) anastomosed to the superior trochlear artery (STA).Methods The diameter of the STA was measured in 38 (76 sides) computed tomography angiographies (CTAs). Independently, six cadaver heads were used to measure the diameter of the supratrochlear system, and the model was applied to one of them.Results In women, the average diameter of the STA was 2.5 and 2.8 mm2 for the right and left sides, respectively; for men, it was 3.0 and 3.2 mm2, respectively. In cadavers, the average diameter of both STA was 2.5 mm2. There was no statistical difference when comparing the right and left STA diameters between the CTA from women and men (p < 0.208 and < 0.492, respectively). An FLFF advanced through the nose was anastomosed to the STA to reconstruct the anterior skull base.Conclusion The STA is a constant vessel with a 2.5 to 3.0 mm2 diameter in men and women that can be used as a recipient free flap vessel. The FLFF can cover the entire skull base. This is a novel method to reconstruct the anterior skull base when local flaps are not available.
Keywords: the superior trochlear system; anterior skull base; anterolateral thigh fascia lata; free flap